GENRE FEATURES OF “LAMENT ON THE CAPTURE AND ULTIMATE DESTRUCTION OF THE HIGHEST AND MOST LUCENT OF THE MOSCOW STATE” - Il’icheva, V.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
The article analyzes the compositional structure and genre are determined by the signs of the solemn speech on the basis of the rhetorical works of the unknown author of the XVII century. The study showed that the peculiarity of this literary monument is the combination of two genres of solemn eloquence - the praise and the weeping in one oratorical work. A distinctive feature of “Lament” is the author’s desire not only to state the fact of the ruin of the state, but to introduce its own interpretation of the causes of the events and the way of salvation of the state.